A peptide-based coating toolbox to enable click chemistry on polymers, metals, and silicon through sortagging - Noeth, Maximilian; Zou, Zhi; El-Awaad, Islam; Lencastre Novaes, Leticia C. de; Dilarri, Guilherme [UNESP]; Davari, Mehdi D.; Ferreira, Henrique [UNESP]; Jakob, Felix; Schwaneberg, Ulrich (Wiley-Blackwell, 2021)
A versatile peptide-based toolbox for surface functionalization was established by a combination of a universal material binding peptide (LCI-anchor peptide) and sortase-mediated bioconjugation (sortagging). This toolbox facilitates surface functionalization either as a one- or a two-step strategy. In the case of the one-step strategy, the desired functionality was directly introduced to LCI. For the two-step strategy, LCI was modified with a reactive group, which can be further functionalized (e.g., employing click chemistry). Sortagging of LCI, employing sortase A from Staphylococcus aureus, was achieved with six different amine compounds: dibenzocyclooctyne amine, biotin-polyethylene glycol amine, Cyanine-3 amine, methoxypolyethylene glycol amine (Mn = 5000 Da), and 2,2,3,3,4,4,4-Heptafluorobutylamine. The purification of LCI-amine sortagging products was performed by a negative purificationusing Strep-tag II affinity chromatography, resulting in LCI-amine conjugates with purities >90%. For the two-step strategy, the LCI-dibenzocyclooctyne sortagging product was purified and enabled, through copper-free azide-alkyne click chemistry, universal surface functionalization of material surfaces such as polypropylene, polyethylene terephthalate, stainless steel, gold, and silicon. The click reaction was performed before or after surface binding of LCI-dibenzocyclooctyne. Finally, in the case of the one-step strategy, polypropylene was directly functionalized with Cyanine-3 and biotin-polyethylene glycol amine.
Keywords: adhesion promoter; anchor peptide; click chemistry; sortase‐ mediated ligation; surface functionalization